Synthesis and Characterization of Nano Silica from Rice Husk - Pokhrel, Shanta; Dahal, Sanjeeb (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
The rice process produces a large amount of rice husk which is most economically important a natural source of silica. In this work, the nano silica was synthesized from dried and cleaned rice husk by treating with hydrochloric acid followed by incineration at 700 ℃ in muffle furnace. Thus, formed silica nanoparticles were characterized through X-ray diffraction (XRD), Fourier-transform infra-red spectroscopy (FTIR) and Energy dispersive X-ray spectroscopy (EDX). The FTIR results showed different peaks at 800 cm-1, 1078 cm-1 and 455 cm-1 resembling the peaks of Si-O symmetric stretching frequency, Si-O asymmetric stretching frequency and Si-O-Si bending frequency respectively. The average crystallite size was found 39.49 nm from XRD results. Whereas, EDX results showed silica elements with 58.20% composition along with Fe and Cr as major impurities. Thus, agricultural waste i.e. rice husk was found to be a major source of silica.